Penerapan Model Project Based Learning (PjBL) Berbasis Pendidikan Lingkungan Hidup terhadap Hasil Belajar IPAS Siswa Kelas IV Sekolah Dasar - Priska Ayu Nawang Wulan; Rita Kusumah (Mataram University, 2026)
Teacher-centered instruction in the IPAS (integrated Science and Social Studies) subject has left many fourth-grade students at SD Negeri 2 Bayuning struggling to reach the minimum mastery criterion, a concern made more urgent by ongoing environmental pressures in the Kuningan area, including uncontrolled waste. This study set out to determine whether combining Project Based Learning (PjBL) with Environmental Education could raise both students' cognitive achievement and their environmental care attitude. Using a quantitative, Quasi-Experimental approach with a Nonequivalent Control Group Design, the researcher worked with 39 fourth-graders split into an experimental group (n = 20) and a control group (n = 19). The experimental group carried out a hands-on